2011
DOI: 10.1111/j.1365-2672.2011.04992.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous feeding of antimicrobial growth promoters to commercial swine during the growing/finishing phase does not modify faecal community erythromycin resistance or community structure

Abstract: Aims:  To investigate the effect of continuous feeding of antimicrobial growth promoters (tylosin or virginiamycin) on the swine faecal community. Methods and Results:  The study consisted of two separate on‐farm feeding trials. Swine were fed rations containing tylosin (44 or 88 mg kg−1 of feed) or virginiamycin (11 or 22 mg kg−1 of feed) continuously over the growing/finishing phases. The temporal impact of continuous antimicrobial feeding on the faecal community was assessed and compared to nondosed control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Accordingly, Castillo et al (2007) found no impact on the abundance of lactobacilli and enterobacteria when different fibre concentrations were included in diets starting at 8 weeks of age. In another study, the use of in-feed antibiotics beginning in the growing phase failed to produce a shift in the fecal bacterial community of swine, as measured using a clone library (Kalmokoff et al 2011). Conversely, dietary studies commencing at weaning (16-28 days) have demonstrated notable changes in bacterial DGGE profiles (Konstantinov et al 2003;Namkung et al 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, Castillo et al (2007) found no impact on the abundance of lactobacilli and enterobacteria when different fibre concentrations were included in diets starting at 8 weeks of age. In another study, the use of in-feed antibiotics beginning in the growing phase failed to produce a shift in the fecal bacterial community of swine, as measured using a clone library (Kalmokoff et al 2011). Conversely, dietary studies commencing at weaning (16-28 days) have demonstrated notable changes in bacterial DGGE profiles (Konstantinov et al 2003;Namkung et al 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Several investigations in broiler chickens indicated that the community structure was altered by AGP treatment concurrent with increased body weight222324. Conversely, other studies in beef cattle, chickens, and pigs concluded that bacterial communities were not altered by AGP treatment252627, although variations in individual taxa were observed in some of these studies2628293031. The differing effects of AGP may be attributed, at least in part, to the complexity of the microbial communities within the GIT in the different animal species and complex interactions between intestinal bacteria and the host.…”
Section: Discussionmentioning
confidence: 99%
“…21% and 32%) [73]. However, according to other previous studies [105,106], background levels of erythromycin and macrolide resistance in nonmedicated swine fecal and manure bacterial communities can already be as high as approximately 40% and are enhanced further by the administration of compounds with antimicrobial activities [62][63][64]. In our study, tylosin had last been used 31 days and 4-4.5 months prior to the last pit emptying and days of sampling, respectively, and consequently was not detected by HPLC in the manure.…”
Section: Discussionmentioning
confidence: 81%